Business model agroecological characteristics of dairy value chain stakeholders in Bobo-Dioulasso - Sib, Ollo; Ouattara, Désiré S.; Orounladji, Michel; Traore, Issouf; Sanogo, Souleymane; Sodre, Etienne; Traore, Arahama; Corniaux, Christian; Vall, Eric (2024)
This document presents the Agroecological Business Model of stakeholders operating upstream in BoboDioulasso's, Burkina Faso dairy value chain (agro-pastoral dairy farmers, mini-dairy farms, milk collection centres, independent collectors, processing units using local milk and processing units using milk powder) which was submitted, discussed and approved by the stakeholders and local dairy value chain players of the Agroecology Living Landscape.